Growth, Trade, and Urban Development of Staple Regions - Hum, Derek; Phillips, Paul (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
Certain themes in historical and contemporary studies of the economic development of Canada remain important. Among these are the staple approach to interpreting Canadian economic development, the notion of Canada as a collection of regional economies, and the distinction between metropolis and hinterland. These themes are both fundamental and interrelated; indeed, they are manifestations of a common process — that of a resource-dependent economic expansion. This paper relates the urbanization and development of staple regions to such determinants as trade, growth, and economic structure. We integrate the metropolis-hinterland framework within the broader staple approach and provide a synthesis of various aspects of economic theory, particularly trade and economic structure, export-led growth of a small, open economy, and the disequilibrium dynamics of urban development — all reinterpreted within the special context of the staple economy. While our major aim is to provide a formal synthesis of the staple approach and urban development, ultimately for policy guidance, references to Canadian economic and historical development are made throughout.